The Mediating Effect of Supply Chain Integration on Inculcation of Islamic ethical values among Muslim students through the e-learning platform - Syarif Syarif (International Journal of Supply Chain Management, 2020)
Abstract– Supply chain Management has played a significant role in corporate efficiency and has attracted the attention of numerous academicians over the last few years. As the concept of becomes more widely accepted, supply chain integration (SCI) is gaining more attention among both practitioners and academics. With an all-encompassing pace of communication and information technology, the planet is changing over time; the gap between the rich and the poor is widening. The study employed a quasi-experimental research design to assess the effectiveness of inculcating Islamic values and supply chain using e-learning platform modality. Teaching moral values is perceived to be an important part of education in Islam. The components of the syllabic formal education slowly spit out information on the growth of character. With both the busy schedule of individuals, the position of family and community in the formation of personality is declining. There was only hope for this country with the teacher on the eLearning site, optimism always fades due to the physical absence of a teacher. This article is a short report showed that the use of e-learning platform with the integration of Islamic values is found effective to enhance students’ Islamic values. It also suggests an ICT-based model that can help to define the growth of Muslim students in the e-Learning environment.